Additive Manufacturing as an Alternative to Core Sampling in Concrete Strength Assessment - Darya Anop; Marzhan Sadenova; Nail Beisekenov; Olga Rudenko; Zulfiya Aubakirova; Assel Jexembayeva (Applied Sciences)
Additive manufacturing reshapes concrete construction, yet routine strength verification of printed elements still depends on destructive core sampling. This study evaluates whether standard 70 mm cubes—corrected by a single factor—can provide an equally reliable measure of in situ compressive strength. Five Portland-cement mixes, with and without ash-slag techno-mineral filler, were extruded into wall blocks on a laboratory 3D printer. For each mix, the compressive strengths of the cubes and ∅ 28 mm drilled cores were measured at 7, 14 and 28 days. The core strengths were consistently lower than the cube strengths, but their ratios remained remarkably stable: the transition coefficient clustered between 0.82 and 0.85 (mean 0.83). Ordinary least-squares regression of the pooled data produced the linear relation <semantics><mover accent="true">R^</mover>core</semantics> [MPa] = 0.97 <semantics><mover accent="true">R^</mover>cube</semantics> − 4.9, limiting the prediction error to less than 2 MPa (under 3% across the 40–300 MPa range) and outperforming more complex machine-learning models. Mixtures containing up to 30% ash-slag filler maintained structural-grade strength while reducing clinker demand, underscoring their sustainability potential. The results deliver a simple, evidence-based protocol for non-destructive strength assessment of 3D-printed concrete and provide quantitative groundwork for future standardisation of quality-control practices in additive construction.